Contribution of Game-Based Learning in Enhancing the Implementation of Learner-Centred Approach in Public Primary schools in Kahama Municipality, Tanzania - Joel, Night; Ndomba, Raymond; Mhagama, Michaela (International Journal For Research In Educational Studies, 2023)
This study assessed game-based learning in enhancing the implementation of learner-centred approach in public primary schools in Kahama Municipality. Specifically, the study intended to find out the contributions of game-based learning in enhancing the implementation of a learner-centred approach in public primary schools. The study was guided by the constructivism theory of learning founded by a Swiss psychologist, Jean Piaget and Lev Vygotsky, a Soviet Psychologist in the 20th century. The study employed mixed research approach with cross-sectional survey design. The study involved 265 participants who were selected through stratified and purposive sampling. Data were collected through questionnaire and structured interview. The data were analysed using descriptive statistics through SPSS version 23 and thematic procedures. The findings revealed that game-based learning (GBL) contributes to the development of creativity, lesson interest, problem-solving skill, collaboration and long lasting memory. It also builds critical thinking skill, expression ability and confidence. Moreover, it lessens absenteeism and provides fun among pupils in enhancing the implementation of LCA. The study recommends the need for educational stakeholders, including the government through the Ministry of Education, Science and Technology to set short, medium and long-term plans for ensuring that game-based learning is used effectively to enhance the implementation of learner-centred approach in schools, policy makers should design a time bound for primary school teachers to upgrade their education in their career after being employed for the effective usage of GBL in the classroom instructions and the curriculum developers should directly document GBL in the curriculum to easy its spread among educational instructors and supervisors all over the country to be align with the rapid world changes.